Drill bit and tool bit composition, tool bit as well as preparation method and application of tool bit
By adding B4C powder to the drill bit cutting head composition and adopting a three-layer structure design, the problems of low processing efficiency and short service life of existing sapphire drill bits are solved, and more efficient processing and longer service life are achieved.
Patent Information
- Application Number
- CN202411593620.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing processing sapphire drill bits have problems with low processing efficiency and short service life, which leads to insufficient application in the optoelectronic semiconductor industry.
Using a drill bit cutting head composition, including carcass components and diamond, the self-sharpness is improved by adding B4C powder to the formula, and a three-layer structure design is adopted, in which the diamond particle size of the edge layer is thinner than that of the intermediate layer and has a higher volume concentration. The diamond volume concentration of the intermediate layer decreases and the particle size becomes coarse.
It significantly improves the efficiency and surface quality of processing sapphires, extends the service life of the cutter head, increases its processing efficiency by more than 30%, and has a significantly higher life than its peer products, reaching the international advanced level.
Smart Images

Figure CN119464871A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hard and brittle material processing, and in particular relates to a drill bit composition, a bit and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the optoelectronic semiconductor industry, the requirements for material processing have become increasingly higher. The efficiency and quality of processing are particularly important in the sapphire field. At present, there are problems such as low processing efficiency and short service life in the processing of sapphire drill bits, which are significantly different from those of foreign competitors.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention aims to provide a drill bit composition, a bit and a preparation method and application thereof. Adding B4C powder to the formula of the drill bit composition of the present invention can effectively improve the self-sharpening property of the matrix, play an auxiliary cutting effect, and help improve processing efficiency. The bit of the present invention adopts a three-layer structure design. At the same time, by reducing the volume concentration of diamonds in the middle layer and coarsening the particle size, the efficiency of sapphire processing can be effectively improved. The diamond particle size of the designed side layer is finer than that of the diamond in the middle layer, which can significantly improve the surface quality of the processed sapphire crystal rod. The three-layer structure design can improve the chip holding and chip removal capabilities of the bit. This bit can be welded to the steel matrix of the drill bit to drill and cut materials such as sapphire, monocrystalline silicon, polycrystalline silicon and jade, solving the problems of low processing efficiency and short service life of sapphire drill bits.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, a drill bit composition comprises a matrix component and diamond, wherein the matrix component comprises: 40-60wt% of ultrafine FeCoNi, 25-45wt% of ultrafine Co, 10-20wt% of ultrafine CuSn, and 1-5wt% of B4C.
[0007] Furthermore, the diamond has a particle size of 100-200 μm and a volume concentration of 40%-60%.
[0008] Furthermore, the diamond has a particle size of 350-600 μm and a volume concentration of 15%-30%.
[0009] Further, the laser particle size D50 of the ultrafine FeCoNi alloy powder is 3-6 μm; and / or, the laser particle size D50 of the ultrafine Co is 1-5 μm; and / or, the laser particle size D50 of the ultrafine CuSn is 10-15 μm; and / or, the laser particle size D50 of the B4C is 20-35 μm.
[0010] In the second aspect, a drill bit made of the drill bit composition described in the first aspect comprises a three-layer structure of an edge layer 1, an intermediate layer 2 and an edge layer 3, wherein the intermediate layer 2 is located between the edge layer 1 and the edge layer 3; wherein the drill bit composition used in the edge layer 1 and the edge layer 3 is the same, and compared with the drill bit composition used in the intermediate layer 2, the diamond has a finer particle size and a higher volume concentration.
[0011] Furthermore, in the drill bit composition of the edge layer 1 and the edge layer 3, the diamond particle size is 100-200 μm, and the volume concentration is 40%-60%; in the drill bit composition of the middle layer 2, the diamond particle size is 350-600 μm, and the volume concentration is 15%-30%.
[0012] In a third aspect, a method for preparing a cutter head as described in the second aspect is provided, wherein layered granulation is performed according to the formula ingredients, followed by material distribution, high cold pressing molding and hot pressing sintering to obtain the cutter head.
[0013] Furthermore, the high cold pressing pressure is 600-800MPa;
[0014] And / or, the hot pressing sintering is performed under a pressure of 30-40 MPa and a temperature of 860-880°C.
[0015] Furthermore, during the granulation, 30 g / kg of granulating agent is added, and 100 ml / kg of isopropanol solvent is added at the same time, and the mixture is evenly stirred with the powder of the formula components and then passed through a 24# sieve, naturally dried after sieving, and finally passed through a 30# sieve.
[0016] In a fourth aspect, an application of a cutter head as described in the second aspect or a cutter head prepared by the preparation method as described in the third aspect, wherein the cutter head is welded to a drill steel substrate for drilling sapphire, single crystal silicon, polycrystalline silicon and jade.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The drill bit composition provided by the present invention adds stronger B4C powder in the formula as an auxiliary abrasive to significantly improve the sharpness of the drill bit, effectively improve the self-sharpening property of the matrix, play an auxiliary cutting effect, and help improve processing efficiency. At the same time, the alloy powder is used in combination with the metal element powder, so that the drill bit is more fully alloyed, the structure is more delicate, and the performance is better after sintering, especially the sintering strength of the iron-cobalt-nickel alloy and the self-sharpening property of the bit are better.
[0019] 2. The cutter head of the present invention adopts a three-layer structure design. The matrix composition formula of each layer is the same, but the diamond volume concentration and particle size are different. By reducing the diamond volume concentration of the middle layer and coarsening the particle size, the efficiency of processing sapphire can be effectively improved, and the processing efficiency can be improved by more than 30%. The diamond particle size of the designed edge layer is finer than that of the middle layer diamond, which can significantly improve the surface quality of the processed sapphire crystal rod. The three-layer structure design can improve the chip holding and chip removal capabilities of the cutter head. The invented cutter head has a service life significantly higher than that of peer products when processing hard and brittle materials such as sapphire, and is at the international advanced level.
[0020] 3. The cutter head of the present invention has a simple preparation method, is easy to process and shape, and can be welded to a drill bit steel substrate to drill and cut materials such as sapphire, single crystal silicon, polycrystalline silicon and jade.
[0021] 4. The method for preparing the tool head of the present invention improves the compressibility and fluidity of the powder through granulation treatment to avoid diamond segregation, and adopts high pressure pressing during cold pressing to make the density reach more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a schematic diagram of a three-layer drill bit of the present invention, wherein 1, 3 are side layers, and 2 is a middle layer. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0025] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0026] According to a first aspect of the present invention, a drill bit composition comprises a matrix component and diamond, wherein the matrix component comprises: 40-60wt% ultrafine FeCoNi, 25-45wt% ultrafine Co, 10-20wt% ultrafine CuSn, and 1-5wt% B4C.
[0027] The drill bit composition provided by the present invention adds stronger B4C powder in the formula as an auxiliary abrasive to significantly improve the sharpness of the drill bit, effectively improve the self-sharpening property of the matrix, play an auxiliary cutting effect, and help improve processing efficiency. At the same time, the alloy powder is used in combination with the metal element powder, so that the drill bit is more fully alloyed, the structure is more delicate, and the performance is better after sintering, especially the sintering strength of the iron-cobalt-nickel alloy and the self-sharpening property of the drill bit are better. Specifically, the content of ultrafine FeCoNi can be typically but not limited to 41wt%, 43wt%, 45wt%, 47wt%, 49wt%, 51wt%, 53wt%, 55wt%, 57wt%, 59wt%, etc., the content of ultrafine Co can be typically but not limited to 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, 42wt%, 44wt%, etc., the content of ultrafine CuSn can be typically but not limited to 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, etc., the content of B4C can be typically but not limited to 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, etc.
[0028] As an optional embodiment of the drill bit composition of the present invention, the diamond has a particle size of 100-200 μm (such as 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, etc.), and a volume concentration of 40%-60% (such as 41%, 43%, 45%, 47%, 49%, 51%, 53%, 55%, 57%, 59%, etc.).
[0029] As an optional embodiment of the drill bit composition of the present invention, the diamond has a particle size of 350-600μm (such as 360μm, 380μm, 400μm, 420μm, 440μm, 460μm, 480μm, 500μm, 520μm, 540μm, 560μm, 580μm, etc.), and a volume concentration of 15%-30% (such as 16%, 17%, 18%, 19%, 21%, 23%, 25%, 27%, 29%, etc.).
[0030] In the above technical solution, diamonds with small particle size and large volume concentration are preferentially used as the outer layer, while diamonds with large particle size and small volume concentration are used as the inner layer, so that the drill bit has a three-layer structure consisting of two outer layers sandwiching the inner layer. The processing quality of the drill bit and the sharpness and life of the drill bit are guaranteed by the distribution of diamond particle size and volume concentration at different positions of the drill bit.
[0031] As an optional embodiment of the drill bit composition of the present invention, the ultrafine FeCoNi alloy powder has a laser particle size D50 of 3-6 μm; and / or, the ultrafine Co laser particle size D50 is 1-5 μm; and / or, the ultrafine CuSn laser particle size D50 is 10-15 μm; and / or, the B4C laser particle size D50 is 20-35 μm.
[0032] In the above technical solution, the particle sizes of ultrafine FeCoNi alloy powder, ultrafine Co, ultrafine CuSn and B4C are used in combination, so that the drill bit has good sharpness and the processed material does not break. It can avoid the breakage of the processed material due to excessive particle size, and also avoid the poor sharpness of the drill bit due to too small particle size. Specifically, the laser particle size D50 of the ultrafine FeCoNi alloy powder can be typically but not limited to 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, etc.; the ultrafine Co laser particle size D50 can be typically but not limited to 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, etc.; the ultrafine CuSn laser particle size D50 can be typically but not limited to 10 .5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, etc.; the laser particle size D50 of B4C is typically but not limitedly selected to be 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, etc.
[0033] According to a second aspect of the present invention, a drill bit made of the drill bit composition of the first aspect comprises a three-layer structure of an edge layer 1, an intermediate layer 2 and an edge layer 3, wherein the intermediate layer 2 is located between the edge layer 1 and the edge layer 3; wherein the drill bit composition used in the edge layer 1 and the edge layer 3 is the same, and compared with the drill bit composition used in the intermediate layer 2, the diamond has a finer particle size and a higher volume concentration.
[0034] The cutter head provided by the present invention adopts a three-layer structural design. At the same time, by reducing the diamond volume concentration of the middle layer 2 and coarsening the particle size, the efficiency of processing sapphire can be effectively improved. The diamond particle size of the designed side layer is finer than that of the middle layer diamond, which can significantly improve the surface quality of the processed sapphire crystal rod. The three-layer structural design can improve the chip holding and chip removal capabilities of the cutter head. The invented cutter head has a service life significantly higher than that of similar products when processing hard and brittle materials such as sapphire, and is at the international advanced level.
[0035] As an optional embodiment of the drill head of the present invention, in the drill head composition of the edge layer 1 and the edge layer 3, the diamond particle size is 100-200 μm, and the volume concentration is 40%-60%; in the drill head composition of the middle layer 2, the diamond particle size is 350-600 μm, and the volume concentration is 15%-30% 。
[0036] In the above technical solution, the cutter head is composed of a side layer 1, an intermediate layer 2 and a side layer 3. The cutter head has a three-layer structure. The formula of the side layer 1 and the side layer 3 is: ultrafine FeCoNi 40-60wt%, ultrafine Co 25-45wt%, ultrafine CuSn 10-20wt%, B4C1-5wt%, the diamond particle size is 100-200μm, and the diamond volume concentration is 40%-60%. The matrix component formula of the intermediate layer 2 is the same as that of the side layer 1, the diamond particle size is 350-600μm, and the diamond volume concentration is 15%-30%. Through the three-layer structure design, the use of B4C in the matrix component, especially the matching of the diamond particle size and volume concentration in the intermediate layer and the side layer, the processing efficiency of sapphire processing is improved by more than 30%; and exceeding the corresponding particle size and concentration will affect the processing quality of the drill bit and the sharpness and life of the drill bit.
[0037] According to a third aspect of the present invention, a method for preparing a cutter head as described in the second aspect comprises performing layered granulation according to the formula ingredients, and then performing material distribution, high-pressure cold pressing and hot pressing sintering to obtain the cutter head.
[0038] In the preparation method of the present invention, the compressibility and fluidity of the powder are improved by granulation treatment to avoid diamond segregation. High pressure pressing is adopted during cold pressing so that the density of the cold pressed blank reaches more than 90%. Furthermore, burr treatment can be performed after hot pressing and sintering, and finally the powder can be welded to the substrate and used as a drill bit.
[0039] As an optional embodiment of the preparation method of the present invention, during the granulation, 30 g / kg of granulating agent is added, and 100 ml / kg of isopropanol solvent is added at the same time, and the mixture is evenly stirred with the powder of the formula components and passed through a 24# sieve, naturally dried after sieving, and finally passed through a 30# sieve.
[0040] In the above technical solution, the granulating agent can be selected from organic matter with the component of CHO, and the amount of addition should not be too much or too little. Too much addition will cause agglomeration, affecting the performance of the drill bit, and too little will lead to poor granulation particles, causing diamond segregation during pressing. Since the powder will agglomerate after adding the granulating agent and the solvent, it needs to be sieved, first through the 24# sieve and then through the 30# sieve to ensure good uniformity of the pressed green body during cold pressing.
[0041] As an optional embodiment of the preparation method of the present invention, the high cold pressing pressure is 600-800 MPa (such as 610 MPa, 630 MPa, 650 MPa, 670 MPa, 690 MPa, 710 MPa, 730 MPa, 750 MPa, 770 MPa, 790 MPa, etc.).
[0042] As an optional embodiment of the preparation method of the present invention, the hot pressing sintering pressure is 30-40MPa (such as 31MPa, 32MPa, 33MPa, 34MPa, 35MPa, 36MPa, 37MPa, 38MPa, 39MPa, etc.), and the temperature is 860-880°C (such as 861°C, 863°C, 865°C, 867°C, 869°C, 871°C, 873°C, 875°C, 877°C, 879°C, etc.).
[0043] According to a fourth aspect of the present invention, an application of the cutter head as described in the second aspect is to weld the cutter head to a drill steel substrate for drilling materials such as sapphire, single crystal silicon, polycrystalline silicon and jade.
[0044] In order to more clearly illustrate the characteristics and advantages of the present invention, the present invention is described in detail using the following examples and comparative examples.
[0045] Embodiment 1:
[0046] First, the materials for the side layer 1 and the side layer 3 are prepared, and the metal powders are accurately weighed by weight: 52 parts of ultrafine FeCoNi, 30 parts of ultrafine Co, 15 parts of ultrafine CuSn, and 3 parts of B4C. The volume concentration of diamond in the side layer 1 and the side layer 3 is 40%, and the particle size is 120μm; then the materials for the middle layer 2 are prepared, and the metal powders are accurately weighed by weight: 52 parts of ultrafine FeCoNi, 30 parts of ultrafine Co, 15 parts of ultrafine CuSn, and 3 parts of B4C. The volume concentration of diamond in the middle layer 2 is 20%, and the particle size is 500μm; in addition, the laser particle size D50 of the ultrafine FeCoNi in the three-layer material is 5μm, the laser particle size D50 of the ultrafine Co is 2.5μm, the laser particle size D50 of the ultrafine CuSn is 12μm, and the laser particle size D50 of the B4C is 26μm;
[0047] The prepared edge layer 1 material, middle layer 2 material and edge layer 3 material are mixed and granulated respectively, specifically including: mixing for 3 hours on a three-dimensional mixer, granulating after mixing evenly, adding 30g / kg of granulating agent during granulation, adding 100ml / kg of isopropyl alcohol solvent at the same time, mixing evenly with the powder, passing through a 24# sieve, drying naturally after sieving, and finally passing through a 30# sieve. The granulation treatment improves the compressibility and fluidity of the powder, and then the granulated powder is cold-pressed, the pressure is 700MPa, the holding time is 1s, and the edge layer 3 material is first laid, then the middle layer 2, and finally the edge layer 1, and pressed together into a three-layer structure with a density of more than 90%. The pressed blanks are assembled into a graphite mold for hot pressing and sintering. The sintering holding temperature is 880°C, the sintering holding pressure is 25MPa, and the sintering holding time is 150s. After sintering, a three-layer drill bit is obtained. The drilling efficiency of sapphire reaches 26mm / min, the service life is 15 meters, and the processed sapphire crystal rod has high surface quality and no edge collapse.
[0048] Embodiment 2:
[0049] First, the materials for the side layer 1 and the side layer 3 are prepared, and the metal powders are accurately weighed by weight: 50 parts of ultrafine FeCoNi, 35 parts of ultrafine Co, 10 parts of ultrafine CuSn, and 5 parts of B4C. The volume concentration of diamond in the side layer 1 and the side layer 3 is 45%, and the particle size is 150μm. Then, the materials for the middle layer 2 are prepared, and the metal powders are accurately weighed by weight: 50 parts of ultrafine FeCoNi, 35 parts of ultrafine Co, 10 parts of ultrafine CuSn, and 5 parts of B4C. The volume concentration of diamond in the middle layer 2 is 15%, and the particle size is 400μm. In addition, the laser particle size D50 of ultrafine FeCoNi in the three-layer material is 3.5μm, the laser particle size D50 of ultrafine Co is 2μm, the laser particle size D50 of ultrafine CuSn is 13μm, and the laser particle size D50 of B4C is 22μm.
[0050] The prepared edge layer 1 material, middle layer 2 material and edge layer 3 material are mixed and granulated respectively, specifically including: mixing for 3 hours on a three-dimensional mixer, granulating after mixing evenly, adding 30g / kg of granulating agent during granulation, adding 100ml / kg of isopropyl alcohol solvent at the same time, mixing evenly with the powder, passing through a 24# sieve, drying naturally after sieving, and finally passing through a 30# sieve. The granulation treatment improves the compressibility and fluidity of the powder, and then the granulated powder is cold-pressed, the pressure is 700MPa, the holding time is 1s, and the edge layer 3 material is first laid, then the middle layer 2, and finally the edge layer 1, and pressed together into a three-layer structure with a density of more than 90%. The pressed blanks are assembled into a graphite mold for hot pressing and sintering. The sintering holding temperature is 860°C, the sintering holding pressure is 25MPa, and the sintering holding time is 150s. After sintering, a three-layer drill bit is obtained. The drilling efficiency of sapphire reaches 30mm / min, the service life is 13.5 meters, and the processed sapphire crystal rod has high surface quality and no edge collapse.
[0051] Example 3
[0052] The only difference from Example 1 is that the three layers of the drill head material each contain 1 portion of B4C.
[0053] The rest of the settings are the same as those in Example 1.
[0054] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 16mm / min and the service life was 11 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0055] Example 4
[0056] The only difference from Example 1 is that the laser particle size D50 of B4C in the three-layer material of the drill head is 30 μm.
[0057] The rest of the settings are the same as those in Example 1.
[0058] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 20mm / min and the service life was 10 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0059] Example 5
[0060] The only difference from Example 1 is that the laser particle size D50 of the ultrafine Co in the three-layer material of the drill head is 1 μm.
[0061] The rest of the settings are the same as those in Example 1.
[0062] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 25mm / min and the service life was 14 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0063] Example 6
[0064] The only difference from Example 1 is that the volume concentration of diamond in the drill bit edge layer 1 and the edge layer 3 is 60%.
[0065] The rest of the settings are the same as those in Example 1.
[0066] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 13mm / min and the service life was 20 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0067] Example 7
[0068] The only difference from Example 1 is that the volume concentration of diamond in the drill bit edge layer 2 is 30%.
[0069] The rest of the settings are the same as those in Example 1.
[0070] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 28mm / min and the service life was 12.5 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0071] Example 8
[0072] The only difference from Example 1 is that the matrix components in the three-layer material of the drill bit all include: 40 parts of ultrafine FeCoNi, 35 parts of ultrafine Co, 20 parts of ultrafine CuSn, and 5 parts of B4C.
[0073] The rest of the settings are the same as those in Example 1.
[0074] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 18mm / min and the service life was 15 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0075] Example 9
[0076] The only difference from Example 1 is that the ultrafine FeCoNi laser particle size D50 in the three-layer material of the drill head is 3 μm, the ultrafine Co laser particle size D50 is 1 μm, the ultrafine CuSn laser particle size D50 is 10 μm, and the B4C laser particle size D50 is 20 μm;
[0077] The rest of the settings are the same as those in Example 1.
[0078] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 21mm / min and the service life was 19 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0079] Example 10
[0080] The only difference from Example 1 is that the pressure during the cold pressing of the drill bit is 600 MPa.
[0081] The rest of the settings are the same as those in Example 1.
[0082] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 22mm / min and the service life was 18 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0083] Embodiment 11
[0084] The only difference from Example 1 is that the laser particle size D50 of B4C in the three-layer material of the drill bit is 32 μm.
[0085] The rest of the settings are the same as those in Example 1.
[0086] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 21mm / min and the service life was 13 meters. The surface quality of the processed sapphire crystal rod was high and there was no edge collapse.
[0087] Example 12
[0088] The only difference from Example 1 is that the laser particle size D50 of the ultrafine Co in the three-layer material of the drill bit is 5 μm.
[0089] The rest of the settings are the same as those in Example 1.
[0090] After sintering, a three-layer drill bit was obtained. The sapphire was tested for drilling efficiency and the results showed that the drilling efficiency could reach 24mm / min and the service life was 11.5 meters. The surface quality of the processed sapphire crystal rod met the requirements and there was no edge collapse.
[0091] Comparative Example 1
[0092] The only difference from Example 1 is that the components in the three-layer structure of the drill bit are all components of the edge layer 1;
[0093] The rest of the settings are the same as those in Example 1.
[0094] After sintering, the drill bit with three layers was tested on sapphire, and the drilling efficiency was found to be 15 mm / min and the service life was 26 meters. Compared with Example 1, although the service life was higher, the drilling efficiency was lower and the surface cracks of the processed crystal rod were more.
[0095] Comparative Example 2
[0096] The only difference from Example 1 is that the components in the three-layer structure of the drill bit are all components of the middle layer 2.
[0097] The rest of the settings are the same as those in Example 1.
[0098] The drill bit with three-layer structure obtained after sintering was tested for sapphire, and the drilling efficiency was found to be 28mm / min and the service life was 8 meters. Compared with Example 1, although the drilling efficiency was improved and the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, the service life was very short.
[0099] Comparative Example 3
[0100] The only difference from Example 1 is that none of the three layers of drill head material contains B4C.
[0101] The rest of the settings are the same as those in Example 1.
[0102] After sintering, the drill bit with three-layer structure was tested on sapphire, and the drilling efficiency was found to be 14mm / min and the service life was 9 meters. Compared with Example 1, although the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, the drilling efficiency was low and the service life was short.
[0103] Comparative Example 4
[0104] The only difference from Example 1 is that the B4C in the three layers of the drill head material is replaced by graphite.
[0105] The rest of the settings are the same as those in Example 1.
[0106] After sintering, the drill bit with three layers was tested for sapphire, and the drilling efficiency was found to be 17 mm / min and the service life was 7.5 meters. Compared with Example 1, although the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, the drilling efficiency was low and the service life was short.
[0107] Comparative Example 5
[0108] The only difference from Example 1 is that the ultrafine FeCoNi in the three-layer material of the drill bit is replaced by ultrafine FeNi and ultrafine Co, and the total mass of the elements before and after the replacement is equal.
[0109] The rest of the settings are the same as those in Example 1.
[0110] After sintering, the drill bit with three-layer structure was tested on sapphire, and the drilling efficiency was found to be 12mm / min and the service life was 13 meters. Compared with Example 1, although the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, the drilling efficiency was low and the service life was short.
[0111] Comparative Example 6
[0112] The only difference from Example 1 is that the ultrafine FeCoNi in the three-layer material of the drill bit is replaced by ultrafine Fe, ultrafine Ni and ultrafine Co, and the ultrafine CuSn is replaced by ultrafine Cu and ultrafine Sn, and the total mass of the elements before and after the replacement is equal.
[0113] The rest of the settings are the same as those in Example 1.
[0114] After sintering, the drill bit with three layers was tested for sapphire, and the drilling efficiency was found to be 20.5 mm / min and the service life was 12 meters. Compared with Example 1, the surface quality of the processed sapphire crystal rod was average, with microcracks, low drilling efficiency and short service life.
[0115] Comparative Example 7
[0116] The only difference from Example 2 is that: the material for the intermediate layer 2 is prepared, and the metal powders are accurately weighed by weight: 50 parts of ultrafine FeCoNi, 35 parts of ultrafine Co, 10 parts of ultrafine CuSn, 0 parts of B4C, the volume concentration of diamond in the intermediate layer 2 is 15%, and the particle size is 400μm.
[0117] The rest of the settings are the same as those in Example 2.
[0118] After sintering, the drill bit with three layers was obtained. The sapphire was tested for material removal. It was found that the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, but the drilling efficiency could only reach 15mm / min and the life was 11 meters. It can be seen that the lack of boron carbide in the inner layer of the drill bit reduces the sharpness and life of the drill bit.
[0119] Comparative Example 8
[0120] The only differences from Example 2 are: (1) the diamond grain size of the side layer 1 and the side layer 3 is 80 μm;
[0121] (2) Prepare the material for the intermediate layer 2. Accurately weigh the metal powders by weight: 50 parts of ultrafine FeCoNi, 35 parts of ultrafine Co, 10 parts of ultrafine CuSn, 0 parts of B4C. The diamond volume concentration of the intermediate layer 2 is 10% and the particle size is 300 μm.
[0122] The rest of the settings are the same as those in Example 2.
[0123] The drill bit with three-layer structure obtained after sintering was tested on sapphire, and it was found that the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, but the drilling efficiency could only reach 9mm / min and the service life was 9 meters. Compared with Example 2, the drilling efficiency was lower and the service life was shorter.
[0124] Comparative Example 9
[0125] The only difference from Example 1 is that when preparing the drill bit, no granulation treatment is performed and the drill bit is directly mixed evenly and then cold pressed.
[0126] The rest of the settings are the same as those in Example 1.
[0127] The drill bit with three-layer structure obtained after sintering was tested on sapphire, and it was found that the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, but the drilling efficiency could only reach 10mm / min and the service life was 8 meters. Compared with Example 1, the drilling efficiency was lower and the service life was shorter.
[0128] Comparative Example 10
[0129] The only difference from Example 1 is that the pressure during the cold pressing of the drill bit is 300 MPa.
[0130] The rest of the settings are the same as those in Example 1.
[0131] The drill bit with three-layer structure obtained after sintering was tested on sapphire, and it was found that the surface quality of the processed sapphire crystal rod was good and there was no edge collapse, but the drilling efficiency could only reach 11mm / min and the service life was 9.5 meters. Compared with Example 1, the drilling efficiency was lower and the service life was shorter.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A drill bit composition, characterized in that: The invention comprises matrix components and diamond, wherein the matrix components comprise: 40-60wt% of ultrafine FeCoNi, 25-45wt% of ultrafine Co, 10-20wt% of ultrafine CuSn and 1-5wt% of B4C.
2. The drill bit composition according to claim 1, characterized in that: The diamond has a particle size of 100-200 μm and a volume concentration of 40%-60%.
3. The drill bit composition according to claim 1, characterized in that: The diamond has a particle size of 350-600 μm and a volume concentration of 15%-30%.
4. The drill bit composition according to any one of claims 1 to 3, characterized in that: The laser particle size D50 of the ultrafine FeCoNi alloy powder is 3-6 μm; and / or, the laser particle size D50 of the ultrafine Co is 1-5 μm; and / or, the laser particle size D50 of the ultrafine CuSn is 10-15 μm; and / or, the laser particle size D50 of the B4C is 20-35 μm.
5. A drill bit made of the drill bit composition according to any one of claims 1 to 4, characterized in that: The drill bit composition comprises a three-layer structure of an edge layer 1, an intermediate layer 2 and an edge layer 3, wherein the intermediate layer 2 is located between the edge layer 1 and the edge layer 3; wherein the drill bit composition used in the edge layer 1 and the edge layer 3 is the same, and compared with the drill bit composition used in the intermediate layer 2, the diamond has a finer particle size and a higher volume concentration.
6. The cutter head according to claim 5, characterized in that: In the drill bit composition of the edge layer 1 and the edge layer 3, the diamond particle size is 100-200 μm, and the volume concentration is 40%-60%; in the drill bit composition of the middle layer 2, the diamond particle size is 350-600 μm, and the volume concentration is 15%-30%.
7. A method for preparing a cutter head as claimed in claim 5 or 6, characterized in that: The cutter head is obtained by performing layered granulation according to the formula ingredients, and then performing material distribution, high-pressure cold pressing molding and hot pressing sintering.
8. The preparation method according to claim 7, characterized in that: The high cold pressing pressure is 600-800MPa; And / or, the hot pressing sintering is performed under a pressure of 30-40 MPa and a temperature of 860-880°C.
9. The preparation method according to claim 7, characterized in that: During the granulation, 30 g / kg of granulating agent and 100 ml / kg of isopropanol solvent are added, and the mixture is uniformly stirred with the powder of the formula components and then passed through a 24# sieve, naturally dried after sieving, and finally passed through a 30# sieve.
10. An application of a cutter head according to claim 5 or 6 or a cutter head prepared by the preparation method according to any one of claims 7 to 9, characterized in that: The cutter head is welded on a drill steel substrate to drill sapphire, single crystal silicon, polycrystalline silicon and jade.